Tackling Antibiotic and Antifungal Resistance in Domestic Animals, Synanthropic Species, and Wildlife: A Global Health Imperative - Tamara Pasqualina Russo; Antonio Santaniello (MDPI AG, 2023)
Antibiotic resistance (ABR) and antifungal resistance (AFR) arise when microorganisms evolve mechanisms to resist pharmacological treatments [...]